Role of Carnoy's solution as treatment adjunct in jaw lesions other than odontogenic keratocyst: a systematic review. Issue 7 (September 2021) - Lal, B.; Kumar, R.D.; Alagarsamy, R.; Shanmuga Sundaram, D.; Bhutia, O.; Roychoudhury, A.
Abstract: Carnoy's solution (CS) is routinely used as adjuvant therapy in the management of odontogenic keratocyst (OKC) and a few other benign lesions. The purpose of this study was to explore the evidence of its application and efficacy in benign lesions other than OKC. We have systematically reviewed published articles to identify the evidence of CS in benign jaw lesions other than OKC following the PRISMA guidelines. The search was conducted in PubMed, Google Scholar, Semantic Scholar, and Cochrane Library database, to find relevant articles from 1980 to March 2020. Finally, 39 studies were analysed in this review. It included studies where CS was used as an adjunct for the benign lesion of the jaw and followed for a minimum of 6 months. Thirty-nine studies with 11 different types of lesion were reported where CS was used as an adjuvant and application time was restricted to 3–5 minutes. Recurrence were reported only in ameloblastoma cases [unicystic = 10.98% (10/91), mixed = 18.18% (26/143)]. Meta-analysis was not possible as all studies were non-controlled in nature. Based on the available data, there was no strong evidence for the use of CS as an adjuvant in the benign lesion of the jaw. Prospective and randomised control studies are recommended for the best stratification for the use of CS.